Pulmonary veno-occlusive disease: An important consideration in patients with pulmonary hypertension. (November 2017) - Balko, Ryan; Edriss, Hawa; Nugent, Kenneth; Test, Victor
Abstract: Pulmonary veno-occlusive disease is a rare subcategory of pulmonary arterial hypertension (WHO Group 1). The disease is poorly understood and difficult to diagnose; it has no definitive cure to date. These patients present with nonspecific symptoms, including dyspnea, exercise intolerance, and weakness. Chest x-rays sometimes differ from idiopathic pulmonary arterial hypertension and may demonstrate alveolar infiltrates and pleural effusions. High resolution computed tomography scans reveal ground glass opacities, interlobular septal thickening, and lymphadenopathy. Echocardiography can estimate the level of pulmonary artery pressures; right heart catheterization is needed for complete hemodynamic characterization of these patients. Lung biopsies demonstrate remodeling of the venules and small veins with intimal and adventitial fibrosis. This can result in total venous occlusion and subsequent recanalization. Similar changes occur in the small arteries and arterioles but are less pronounced than the venous changes. There is no effective medical therapy for these patients, and treatment with the pulmonary arterial hypertension specific medications often causes acute deterioration with pulmonary edema. The recent discovery of the biallelic mutations of the EIF2AK4 gene as an etiology for heritable form of pulmonary veno-occlusive disease increases our understanding of the disease pathogenesis and potentially identifies a future approach to treatment. Without definitive treatment, the prognosis is very poor, and the life expectancy of these patients is much shorter than patients with pulmonary arterial hypertension. These patients need early referral to transplantation centers. Highlights: Some patients with pulmonary arterial hypertension have veno-occlusive disease. Pathologic changes in these patients are centered in small veins and venules. High resolution computed tomography can help make this diagnosis. These patients need early referral to lung transplantation centers. Pulmonary arterial hypertension specific therapy is potentially dangerous.